Ultrasonically spray coated silver layers from designed precursor inks for flexible electronics - Marchal, W; Vandevenne, G; D'Haen, J; Calmont de Andrade Almeida, A; Durand Sola, M A; van den Ham, E J; Drijkoningen, J; Elen, K; Deferme, W; Van Bael, M K; Hardy, A (Nanotechnology, 2017)
Integration of electronic circuit components onto flexible materials such as plastic foils, paper and textiles is a key challenge for the development of future smart applications. Therefore, conductive metal features need to be deposited on temperature sensitive substrates in a fast and straightforward way. The feasibility of these emerging (nano-) electronic technologies depends on the availability of well-designed deposition techniques and on novel functional metal inks. As ultrasonic spray coating (USSC) is one of the most promising techniques to meet the above requirements, innovative metal organic decomposition (MOD) inks are designed to deposit silver features on plastic foils. Various amine ligands were screened and their influence on the ink stability and the characteristics of the resulting metal depositions were evaluated to determine the optimal formulation. Eventually, silver layers with excellent performance in terms of conductivity (15% bulk silver conductivity), stability, morphology and adhesion could be obtained, while operating in a very low temperature window of 70 °C-120 °C. Moreover, the optimal deposition conditions were determined via an in-depth analysis of the ultrasonically sprayed silver layers. Applying these tailored MOD inks, the USSC technique enabled smooth, semi-transparent silver layers with a tunable thickness on large areas without time-consuming additional sintering steps after deposition. Therefore, this novel combination of nanoparticle-free Ag-inks and the USSC process holds promise for high throughput deposition of highly conductive silver features on heat sensitive substrates and even 3D objects.